THE IMPLEMENTATION OF SEMANTIC MAPPING TECHNIQUE IN THE TEACHING OF READING COMPREHENSION - Siti Kholifah; Sudiran Sudiran (ELTR Journal, 2020)
This study aimed to describe the students’ involvement to the implementation of semantic mapping in reading activities and to describe the students’ responses to the implementation of semantic mapping technique in reading activities. This research used a qualitative case study conducted at MTs Maarif Sukorejo - Pasuruan. It involved one class of the eighth grade which consists of 32 students. The data were collected through observation, document interpretation, and interview. The data from the three instruments were analyzed qualitatively. The results of observation and documentation showed that the implementation of semantic mapping could actively involve the students’ reading activities dealing with pre-, whilst-, and post-reading activities at VIII A Grade of MTs. Maarif Sukorejo – Pasuruan. In addition, the results of interview indicated that all students had positive responses to reading activities and the implementation of semantic mapping in the learning of reading comprehension. Dealing with the results of documentation mainly in the field notes, most of students were interested in the implementation of semantic mapping technique such as: vocabulary brainstorming activities, reading aloud, finding detailed information, finding main idea, making a summary and answering question through semantic mapping.